2003
DOI: 10.1046/j.1537-2995.2003.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Collection of MNCs and progenitor cells by two separators for PBPC transplantation: a randomized crossover trial

Abstract: Amicus is superior to Spectra in avoiding apheresis-induced thrombocytopenia caused by platelets contaminating the collected samples. Therefore, the Amicus is useful for patients with thrombocytopenia or with a less-than-normal platelet count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 9 publications
4
59
4
Order By: Relevance
“…One article has reported granulocyte content of Amicus products [5] although the values can be calculated using published data from two other articles [17,18]. These results ranged from 3.2 to 19.3 3 10 9 granulocytes, similar to the content seen in our study, especially considering that the volume of blood processed and the starting WBC counts were higher in the patients that we examined.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…One article has reported granulocyte content of Amicus products [5] although the values can be calculated using published data from two other articles [17,18]. These results ranged from 3.2 to 19.3 3 10 9 granulocytes, similar to the content seen in our study, especially considering that the volume of blood processed and the starting WBC counts were higher in the patients that we examined.…”
supporting
confidence: 80%
“…Most authors reported RBC content in gm of hemoglobin (Hgb) [5,18,19] rather than ml of RBC [17]. Our RBC content ranged from 16 to 32 mL, with the 1.5/6.0 offset setting at 22 mL, higher than reported results, even considering we processed twice as much blood.…”
contrasting
confidence: 56%
“…1 cells was reported superior [4] and comparable to the COBE Spectra [5,6]. The platelet contamination was lower than in other systems [4][5][6].…”
Section: Introductionmentioning
confidence: 58%
“…The platelet contamination was lower than in other systems [4][5][6]. In patients with high WBC precounts, the CE for CD34 1 cells was lower than in those with precounts < 40 G/l.…”
Section: Introductionmentioning
confidence: 64%
“…They found similar collection efficiencies for CD34 þ cells, white blood cells and mononuclear cells but significantly lower collection efficiencies for platelets. 16 Significantly less whole blood was processed in our CS collection compared to the SP collections. This was because of the lower flow rates used for CS.…”
Section: Discussionmentioning
confidence: 97%